2021
DOI: 10.3390/microorganisms9081597
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination Strategies Used for AFB Culture Significantly Reduce the Viability of Mycobacterium abscessus Complex in Sputum Samples from Patients with Cystic Fibrosis

Abstract: Nontuberculous mycobacteria are important respiratory pathogens in patients with cystic fibrosis (CF). For diagnosis, international guidelines recommend culture of sputum that has been decontaminated via chemical treatment. Fifty-six sputum samples from 32 patients known to be previously colonized or infected with NTM were subdivided, and the aliquots were subjected to six different decontamination strategies, followed by quantitative culture for NTM. Thirty sputum samples contained Mycobacterium abscessus com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…We therefore accept that the unambiguous determination of the yield could be skewed by the difficulty of determining the true measurement of the presence of viable mycobacteria in the examined samples (missed blank samples). Yield can be affected of course by the decontamination method due to sensitivity of some mycobacterial species to a decontamination agent [ 66 ]. Cultivation may be (and will be in further work) refined by using special cultivation media (e.g., RGM) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…We therefore accept that the unambiguous determination of the yield could be skewed by the difficulty of determining the true measurement of the presence of viable mycobacteria in the examined samples (missed blank samples). Yield can be affected of course by the decontamination method due to sensitivity of some mycobacterial species to a decontamination agent [ 66 ]. Cultivation may be (and will be in further work) refined by using special cultivation media (e.g., RGM) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sputum samples were then processed using N-acetyl-L-cysteine/sodium hydroxide (NalC/NaOH) to digest the sputa and to reduce the growth of non-acid fast bacilli. [47][48][49] The processed sputum samples were spiked with 10 8 CFU/mL M. smegmatis and were treated with Tre-Cz in the same manner as M. smegmatis. Confocal fluorescence microscopy showed that Tre-Cz could indeed image mycobacteria in sputum.…”
Section: 4mentioning
confidence: 99%
“…However, no mycobacterial growth was detected on culture. This may be attributed to the death of the bacteria in the process of digestion and decontamination of the specimen [ 13 ]. Based on the findings on microbiological examination and lung imaging, we considered the patient to have NTM-PD.…”
Section: Discussionmentioning
confidence: 99%